Securing AI. - Gomo, Tendai; Dai, Jason; Alani, Mohammed M.; Thaine, Patricia; Sengupta, Arijit; Jackson, Ethan C.; Dullerud, Natalie (Superstream series (O'Reilly (Firm)), 2021)
Sponsored by Intel As AI becomes more pervasive, the question of how to build, test, and maintain risk-averse systems grows too. Join experts from the field to learn how they analyze and handle privacy, risk, and safety in their work. About the AI Superstream Series: This four-part series is packed with insights from some of the brightest minds in AI. You'll get a deeper understanding of the latest tools and technologies that can help keep your organization competitive and learn to leverage AI to drive real business results. What you'll learn and how you can apply it Understand what secure AI does (and doesn't) include See what secure AI might look like from design through deployment Discover real-world technical applications of secure AI This recording of a live event is for you because... You're a machine learning engineer or data scientist interested in the challenges of building secure AI and machine learning tools. You want to better understand how industry experts handle security. You want to learn how to improve your AI and machine learning systems. Recommended follow-up: Read (report) AI and the Law.